Body composition and resting energy expenditure in elderly male patients with chronic obstructive pulmonary disease - Sergi, Giuseppe; Coin, Alessandra; Marin, Sara; Vianello, Andrea; Manzan, Alessandro; Peruzza, Silvia; Inelmen, Emine Meral; Busetto, Luca; Mulone, Silvana; Enzi, Giuliano (Respiratory medicine, 2006)
Our study investigates nutritional status, resting energy expenditure (REE) and physical performance in elderly patients with stable COPD to identify any early conditions of hypermetabolism, malnutrition and sarcopenia. Eighty-six males (40 stable COPD and 46 healthy subjects) over 65 years old were studied. All subjects underwent spirometry, blood gas analysis and a 6-min walking test (6MWT). Fat-free mass (FFM) and appendicular skeletal muscle mass (ASMM) were measured by dual energy X-ray absorptiometry (DEXA). REE was measured by indirect calorimetry. COPD patients had a lower FFM both expressed in kilograms and after correction for height squared. The prevalence of sarcopenia was higher for COPD subjects (38% vs 31%). REE, both in absolute values and adjusted for FFM was significantly higher in COPD patients. Hypermetabolism was found in 60% of COPD cases and 13.7% ( P<0.01) of healthy subjects. No relationship was found in COPD patients between the measured/predicted REE ratio (REE m/REE p) and FEV 1. In the hypermetabolic COPD subgroup, the REE m/REE p ratio correlated with 6MWT. Elderly patients with stable COPD develop an increased REE. This hypermetabolism seems to be independent of the severity of the pulmonary obstruction and to influence the patient's physical performance.